Peran Guru Sosiologi Dalam Mengimplementasikan Nilai Pendidikan Karakter, Toleransi Dan Peduli Sosial Melalui Pembelajaran Sosiologi Di SMA Negeri 95 Jakarta - Manurung, Diana Veronika; Kuntari, Septi; Hardiansyah, Muhammad Agus (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study aims to examine the role of sociology teachers in implementing character education values, particularly tolerance and social care, at SMA Negeri 95 Jakarta. The research method used is qualitative, with data collection techniques including interviews, observations, and documentation. The research informants consist of the school principal, sociology teachers, and nine students, totaling eleven informants. The results show that the implementation of character education values, especially tolerance and social care, has been successfully carried out. Sociology teachers play a crucial role in instilling the values of tolerance and social care in classroom learning and through various structured and systematic school programs and activities. These programs include routine school activities such as "Clean Friday," involving the entire school community, which represents diversity. Additionally, these efforts foster attitudes aligned with the school's goals of social care and living harmoniously with existing differences.